2021
DOI: 10.1038/s41591-021-01463-x
|View full text |Cite
|
Sign up to set email alerts
|

A ‘mix and match’ approach to SARS-CoV-2 vaccination

Abstract: Heterologous dosing with the adenovirus-based ChAdOx1 (AstraZeneca) vaccine followed by an mRNA vaccine induced stronger immune responses than did the homologous ChAdOx1 vaccine series, according to recent immunogenicity studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 15 publications
1
44
0
2
Order By: Relevance
“…Additionally, the interval between prime and boost probably has a critical role. In SOTR the combination of two vaccine strategies that offer complementary stimulation of different immune pathways may more effectively induce long-lasting B cell responses and potent T cell responses [27]. The heterologous vaccine schedules, however, might have some short-term disadvantages inducing greater systemic reactogenicity following the boost dose than their homologous counterparts, as shown by preliminary studies [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the interval between prime and boost probably has a critical role. In SOTR the combination of two vaccine strategies that offer complementary stimulation of different immune pathways may more effectively induce long-lasting B cell responses and potent T cell responses [27]. The heterologous vaccine schedules, however, might have some short-term disadvantages inducing greater systemic reactogenicity following the boost dose than their homologous counterparts, as shown by preliminary studies [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Several countries have started combining COVID-19 vaccines, referred to as a heterologous vaccine strategy ( 213 , 214 ). Individuals who had previously received the Oxford-AstraZeneca (AZD1222/ChAdOx1) vaccine were given the Pfizer-BioNTech (BNT162b2) mRNA vaccine after eight weeks ( 215 ).…”
Section: Future Concerns and Considerationsmentioning
confidence: 99%
“…Individuals who had previously received the Oxford-AstraZeneca (AZD1222/ChAdOx1) vaccine were given the Pfizer-BioNTech (BNT162b2) mRNA vaccine after eight weeks ( 215 ). Vaccinees elicited more robust immune responses that generated more antibodies as well as memory B cells than the control group who received the Oxford-AstraZeneca vaccine alone ( 213 – 215 ). The United Arab Emirates recently started administrating Pfizer-BioNTech (BNT162b2) booster shots to individuals six months after the second Sinopharm (BBIBP-CorV) shot ( 216 ).…”
Section: Future Concerns and Considerationsmentioning
confidence: 99%
“…In addition, the strategy will ensure that more people are vaccinated across the world and might be the magic wand needed to reduce the global inequalities in vaccine availability ( 13 ). Deming and Lyke ( 15 ) reported that the mix and match vaccination strategy improved the neutralization of variants ( 16 ) and the induction of spike protein-specific CD8+ T cells beyond what was achieved via homologous vaccinations ( 17 ). Furthermore, Barros-Martins et al ( 16 ) and Schmidt et al ( 17 ) believed that the heterologous combination of Oxford-AstraZeneca vaccine as primer dose and Pfizer–BioNTech Vaccine as booster dose resulted in 20 to >60-fold greater titers of neutralizing antibodies (IgG and IgA) against the alpha, beta, or gamma variants of the SARS-CoV-2.…”
Section: Mix- and Match Approach To Covid-19 Vaccinesmentioning
confidence: 99%